Statins and regression of organ damage - Domenico Panuccio (Italian Journal of Medicine, 2013)
Atherosclerosis develops over the course of 50 years. It is a generally asymptomatic process that begins early in life in response to the stimuli of cardiovascular risk factors. The first step is a lipid retention, oxidation, and modification, which provokes chronic inflammation at susceptible sites in the walls of all major conduit arteries. Initial fatty streaks evolve into fibrous plaques, some of which develop into forms that are vulnerable to rupture, causing thrombosis or stenosis. Erosion of the surfaces of some plaques and rupture of a plaque’s calcific nodule into the artery lumen also may trigger thrombosis. It has been demonstrated that statins significantly affect the prognosis and outcome of patients either with or at risk of having cardiovascular atherosclerotic disease. Several studies suggested an extra-beneficial effect of statins, since they may affect the cardiovascular system beyond their effect on the lipid profile, through pleiotropic effects such as modulation of endothelial function, and reduction of inflammatory and immunological processes in the vascular bed. Thus, these drugs favorably alter atherosclerosis in term of plaque size, cellular composition, chemical composition, and biological activities.